Stakeholder power, sustainability reporting, and corporate governance: A case study of manufacturing industry at Indonesia’s stock exchange - Setiawanta, Yulita; Purwanto, Agus (Univerzita Pardubice, 2019)
This research explains about the way the stakeholder power can affect the implementation of sustainability reporting and the corporate governance at a manufacturing industry in Indonesia listed on Indonesia’s Stock Exchange. The results of this study are expected to provide an overview to prospective foreign investors who are interested in investing in Indonesia public companies which related to organizational behavior and governance style. However, there was less company that reported sustainability reporting continuously from 2007 up to 2016. This becomes a special and interesting concern to be investigated as the awareness phenomenon for the industries in Indonesia. With specified criteria found 60 observation data for 10 years and used multiple linear regression. The result showed that Government Control and Audit Control affected the implementation of Sustainability Reporting while the Internal control and shareholder control had no effect. The special note for shareholder control had a negative coefficient and it became a phenomenon for future research. Another finding was that the implementation of Sustainability Reporting and Government Control had an effect on good corporate governance.
Keywords: stakeholder power; sustainability reporting; corporate governance; government control; audit control; G30; G34; M14; M420